Hubungan Politik Oranisasional dan Organizational Citizenship Behavior - Marliana, . (Kajian Manajemen dan Bisnis, 2011)
Many researches on organizational politics have been done to investigate outcomes of organizational political behavior. Previous researches found that there was no consistent result of the relationship between organizational politics and organizational citizenship behavior (OCB). The purpose of this research was to re-analyze the relationship between organizational politics and organizational citizenship behavior.